2017
DOI: 10.21595/vp.2017.18548
|View full text |Cite
|
Sign up to set email alerts
|

Introducing box-plate beam-to-column moment connections

Abstract: Abstract. Nowadays, using high-ductility structures in the construction and use of significant buildings is highly appreciated. To use more ductile structures, effort has been made in this research to introduce box-plate beam-to-column connections. They underwent hysteretic loading and it was found from their moment-rotation curves that the bending capacity and ductility of the box-plate connection were more than ordinary rigid connection, and those of the latter were more than those of the normal typical one.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…Visible regression models are useful tools to predict the performance of structural elements because engineers can use them easily (Shishegaran et al, 2020a). Sev-eral studies have focused on regression models, such as multiple linear regression (MLR), to predict the performance of beam-to-column connections (Islam and Alam, 2013;Shishegaran et al, 2017Shishegaran et al, , 2018. Multiple natural logarithm (Ln) equation regression (MLnER) has been used to predict the performance of an RC panel under an explosive load.…”
Section: Introductionmentioning
confidence: 99%
“…Visible regression models are useful tools to predict the performance of structural elements because engineers can use them easily (Shishegaran et al, 2020a). Sev-eral studies have focused on regression models, such as multiple linear regression (MLR), to predict the performance of beam-to-column connections (Islam and Alam, 2013;Shishegaran et al, 2017Shishegaran et al, , 2018. Multiple natural logarithm (Ln) equation regression (MLnER) has been used to predict the performance of an RC panel under an explosive load.…”
Section: Introductionmentioning
confidence: 99%
“…where are the stress components for the undamaged material. A lot of work has been done under this concept of mechanical damage [19][20][21][22][23][24][25][26][27][28]. Almost all authors who considered spherical medium in their applications assumed that the body with a spherical cavity avoids the problem of singularity in the center of the sphere.…”
Section: Introductionmentioning
confidence: 99%
“…4. There are various studies available focused on force-deflection and strength of other materials, like concrete and steel bars [19,20], however, since NiTis show super elastic properties by the changes within its internal structure, they have a high potential to be used as actuator alternatives in industrial applications. In this study, an elastic, lightweight, and thin SMA wire has been observed under varying electrical current values.…”
Section: Introductionmentioning
confidence: 99%